A Critical Investigation on the Human Resources Innovation Practices in National Survey Authority (NSA)-Oman - Matriano, Maria Teresa (Advances in Social Sciences Research Journal, 2021)
Purpose: In any organization around the world, the Human Resources Department is considered to be an important division because it is responsible for personnel affairs in the organization through the practices of staff in the Human Resources Department. So much so that it is regarded as a police force that works for stability and security as well as human resources working for the stability of staff in the organization. Because of the importance of the Human Resources Department, the organization should periodically evaluate and verify the processes of innovation and development of the Section if it is consistent with the latest practices of the developed organizations and if the innovation practices are implemented in the required manner or not. Methodology: The survey questionnaire was developed and disseminated among the staff of the National Survey Authority. There were personal interviews with some officials of the National Survey Authority where they were asked questions about innovation practices. Findings: The tests conducted by the NSA in hiring staff was easy. This of course gives the opportunity to those with simple qualification to be qualified and this serves as an innovation for employment in the NSA. NSA randomly identifies the employee’s department to work in, more than relying on qualifications and experience. This leads to the appointment of those who lack experience and eligibility and put the employee in an inappropriate place and this affects the productivity and causes a failure or weakness in the system of innovation. Research Implications: The decline in the level of HR practices will lead to a decline in the level of productivity and also to the resignation of many aspiring employees who were looking for an environment that motivates them. Novelty : Technology as in the case of NSA, has driven hugely human resource innovation practices in an organization. NSA to motivate staff to innovate and help officials in NSA to reach a deeper understanding of the practices of innovation in their practices of human resources which will facilitate the decision-making process in motivating the employee of the organization.